Novel Implications in Molecular Diagnosis of Lynch Syndrome - Raffaella Liccardo; Marina De Rosa; Paola Izzo; Francesca Duraturo (Gastroenterology Research and Practice)
About 10% of total colorectal cancers are associated with known Mendelian inheritance, as Familial Adenomatous Polyposis (FAP) and Lynch syndrome (LS). In these cancer types the clinical manifestations of disease are due to mutations in high-risk alleles, with a penetrance at least of 70%. The LS is associated with germline mutations in the DNA mismatch repair (MMR) genes. However, the mutation detection analysis of these genes does not always provide informative results for genetic counseling of LS patients. Very often, the molecular analysis reveals the presence of variants of unknown significance (VUSs) whose interpretation is not easy and requires the combination of different analytical strategies to get a proper assessment of their pathogenicity. In some cases, these VUSs may make a more substantial overall contribution to cancer risk than the well-assessed severe Mendelian variants. Moreover, it could also be possible that the simultaneous presence of these genetic variants in several MMR genes that behave as low risk alleles might contribute in a cooperative manner to increase the risk of hereditary cancer. In this paper, through a review of the recent literature, we have speculated a novel inheritance model in the Lynch syndrome; this could pave the way toward new diagnostic perspectives.